The Impact of Stress and Impulsivity on Pavlovian Instrumental Transfer in Humans - Tang, Ruoqi (2023)
Pavlovian instrumental transfer (PIT) is a phenomenon thought to underlie the maintenance of addictive behaviours, in which a conditioned stimulus (CS), previously paired with a specific outcome, can influence the performance of an instrumental response (R). PIT can be specific (the CS selectively elevates the performance of an R paired with the same outcome) and general (CSs elevate the performance of any R paired with an outcome of the same motivational value). To study both specific and general PIT effects, an avoidance-based and an appetitive PIT task were conducted in Chapter II. Both effects were observed successfully in the two types of PIT tasks.